'Informal Infrastructure' of Prototyping: Practicing Organisation by Performing Materiality. (September 2022) - García, Sandra Fernández; Valle, Francisco Sánchez
Abstract : In recent years, sheltered by the so-called 'ontological turn' in the social sciences, organisational analysis has paid special attention to artefacts. Nevertheless, there is still a dominant account grounded in a dichotomist view of the subject-object relationship either in teleological (mind-body) or in hylomorfic (form-matter) terms when analysing organising practices. On the contrary, our argument is based on non-dualistic approaches in an attempt to foreground relational aspects of practices. From a practice-based approach, the article addresses the role of three 'prototypes' aimed at the management of the 'air' by citizenship, in the re-configuration of bodies, technics and ethical-political engagement. Specifically, it focuses on the normative dimensions of organising by which knowledges, materials and values converge in the open-ended process of prototyping . The argument is deployed by relying on qualitative research based on multi-sited ethnographic fieldwork, developed both at different workshops and by online ethnography. The main aim of the article is to show how bodies and artefacts are mutually in/trans/formed when negotiating the social implications for the ontological category of 'air'. In doing so, the concept of 'informal infrastructure' is proposed to account for those practices (which appear somewhat contingent, mundane or, at best, taken for granted) by which agents do not only commit to a particular ethical implication embedded in the category of 'air', as a symbolic result, but also to distinctive ways of practicing organisation as a political process of performing materiality. To this end, adopting the analytical concept of 'informal infrastructure' allows to simultaneously consider both the formal and informal aspects that emerge in these collaboration-driven practices, as well as to address their effects on the maintenance within and expansion into other networks.